African Handbook of Climate Change Adaptation 2021
DOI: 10.1007/978-3-030-45106-6_61
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Adaptation: Opportunities for Increased Material Recycling Facilities in African Cities

Abstract: Africa’s urban morphology is expected to develop at a steady rate between 2020 and 2050. Population growth, rising urbanization rates, growing energy consumption, and industrialization are only a few of the reasons causing these changes. Likewise, waste production is projected to rise from 125 million tons in 2012 to 244 million tons annually by 2025. Around 60.0% and 80.0% of African waste is made up of organic material, which is a viable methane source. Fly tipping, free disposal, landfilling, and incinerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Individual anxiety and fear regarding climate change were among the most common determinants that recognize the phenomena as dangerous, along with attitudes and moral norms [26,29,30]. Regarding behavioral efficacy for climate change mitigation, individual actions are believed to be a contributing factor, including recycling and less meat consumption [31][32][33]. In addition, risk perceptions related to climate change [27,34,35] were found to be related to behavioral responses, such as the prediction of and adaptation to climate change [36][37][38].…”
Section: Theoretical Framework 21 Efficacy Of Climate Change Responsementioning
confidence: 99%
“…Individual anxiety and fear regarding climate change were among the most common determinants that recognize the phenomena as dangerous, along with attitudes and moral norms [26,29,30]. Regarding behavioral efficacy for climate change mitigation, individual actions are believed to be a contributing factor, including recycling and less meat consumption [31][32][33]. In addition, risk perceptions related to climate change [27,34,35] were found to be related to behavioral responses, such as the prediction of and adaptation to climate change [36][37][38].…”
Section: Theoretical Framework 21 Efficacy Of Climate Change Responsementioning
confidence: 99%
“…Various types of pollutants can induce biological, chemical, physical, and psychological illnesses, with noise pollution being one of the pollutants that closely relate to our daily lives, thus leading to numerous problems. [1,2,11,12,[3][4][5][6][7][8][9][10] For example, noise pollution can put humans at permanent physical risks such as hyperacusis, misophonia, and hearing loss, or causes mental health problems such as sleep disorder, anxiety, attention deficit hyperactivity disorder, and migraine. [13][14][15][16][17][18][19][20][21] Therefore, there have been many attempts to shape their unit cells and geometries that can affect the wave propagations, modes, and wavelength related to the Bragg band gap whether the size of the unit cell is within the range of photonic or phononic wavelengths.…”
Section: Introductionmentioning
confidence: 99%
“…Wastes are partially responsible to high exposure to diseases such as malaria, water bone diseases, pest's multiplications and more greenhouse gas (GHG) emissions. This is why it is necessary to develop technics and solutions to manage them efficiently with less environmental impact [1]. Among the solutions used, one can enumerate both the energy production (biogas) and the organic liquid fertilizer.…”
Section: Introductionmentioning
confidence: 99%
“…Among the solutions used, one can enumerate both the energy production (biogas) and the organic liquid fertilizer. The importance of energy in national development cannot be over emphasized, energy is the hub around which the development and industrialization of any nation revolved [1]. Several studies have shown that by incorporating renewable energy resources into the overall energy mix or unit of nations, any of the negative environmental impacts of energy used could be avoided or minimized [2,3].…”
Section: Introductionmentioning
confidence: 99%